2019
DOI: 10.1002/jmri.26891
|View full text |Cite
|
Sign up to set email alerts
|

Does traditional asian vegetables (ulam) consumption correlate with brain activity using fMRI? A study among aging adults from low‐income households

Abstract: Background Working memory and cognitive flexibility are supported by the dorsolateral prefrontal cortex (DLPFC). Aging adults from low‐income households are individuals with a high risk of cognitive decline who incorporate ulam in their daily diet. Purpose To examine relationship between ulam consumption and the working memory and cognitive flexibility among aging adults from low‐income households who are more susceptible to cognitive decline. Study Type Cross‐sectional. Population/Subjects Thirty‐two aging ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…33 Interestingly, an earlier study had indicated the involvement of the middle and precentral frontal gyrus in the DLPFC during the SCWT paradigm. 27 Thus, the results in this study indicated that the subjects in the CC supplement group showed a higher increase in left DLPFC activation for the SCWT (congruent), where the left hemisphere showed the maximal brain activity during the allocated word recognition tasks following 12 weeks of supplementation. 4 Recent findings have indicated that the left hemisphere in the brain is significantly affected by any cognitive interference in the color task.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…33 Interestingly, an earlier study had indicated the involvement of the middle and precentral frontal gyrus in the DLPFC during the SCWT paradigm. 27 Thus, the results in this study indicated that the subjects in the CC supplement group showed a higher increase in left DLPFC activation for the SCWT (congruent), where the left hemisphere showed the maximal brain activity during the allocated word recognition tasks following 12 weeks of supplementation. 4 Recent findings have indicated that the left hemisphere in the brain is significantly affected by any cognitive interference in the color task.…”
Section: Discussionmentioning
confidence: 55%
“…For the fMRI task, the N-back task and Stroop Color Word Test (SCWT) paradigms were used in this study. 11,27 N-BACK TASK. The two conditions of the N-back task used in this study included the 0-back and 1-back which had been applied in an earlier study.…”
Section: Fmri Protocolmentioning
confidence: 99%
“…To ensure a clear understanding of the assignment at hand, the participants were provided with a diagram of the task blocks, and the protocol was clearly explained by the field-worker. The two conditions of the N-back task, which were used in this study, had consisted of 0-back and 1-back that were employed by previous studies ( Lau et al, 2018 ; You et al, 2019 ), which had been created and displayed by using the SuperLab 5 (Cedrus, Los Angeles, CA, United States). N-back holds four blocks for every 0-back and 1-back condition.…”
Section: Methodsmentioning
confidence: 99%
“…It showed the highest total phenolic content as compared to nine other common Malaysian traditional vegetables [21]. CC exhibits strong antioxidant properties and may have the ability to prevent neurodegenerative diseases such as dementia [20,22,23]. One of its beneficial based on the medicinal properties are as antidiabetic, anti-obesity, antimicrobial, antihypertensive, and anticancer.…”
Section: Introductionmentioning
confidence: 99%